Prevalence of endometriosis among adolescent school girls with severe dysmenorrhea: A cross sectional prospective study - Ragab, Ahmed; Shams, Maher; Badawy, Ahmed; Alsammani, Mohamed Alkhatim (International Journal of Health Sciences, 2015)
Objectives: To determine the prevalence of endometriosis among adolescent school girls with severe dysmenorrhea. Methodology: Data was collected via interviewed questionnaire. Patients with symptoms and signs suggestive of endometriosis were further evaluated by abdominal ultrasonography (AUS), serum cancer antigen 125 (CA125). Laparoscopy was done for confirmation in those who agreed. Those who declined laparoscopy were offered magnetic resonance imaging (MRI). Results: A total number of 654 adolescents were interviewed. Their mean age was 15.2 ±3.53 SD years. The mean duration of cycles and flow days was 29 ± 8.4 SD and 4 ± 2.8 SD respectively. The age of menarche in years was 13 ± 1.2 SD. Cycles were regular in 77.4 % (n=506) while irregular in 22.6 % (n=148). Of all studied girls, 48.9% (n=320) had menstrual pain of varying degree of severity. Severe dysmenorrhea was reported in 68.8 % (n=220/320) of them. Fifty six of these cases (25.5 %) had ultrasound findings suggestive of endometriosis. CA125 was elevated in41.5 % (n= 27/56) of them. Patients accepted laparoscopic confirmations were 34, of them 79.4%, (n=27) had positive histo-pathological evidence of endometriosis. MRI was offered to those declined laparoscopy (n=22). Endometriosis was suggested in 77.3% of them. Conclusion: The study concluded the prevalence of endometriosis in adolescents with severe dysmenorrhea was 12.3 % despite some declined laparoscopy. The unacceptability of laparoscopy and unfeasibility of local examination and trans-vaginal ultrasound add more to the difficulty of diagnosis. Key words: Adolescent, endometriosis, severe dysmenorrhea.